Hiraya Manawari.Volume 18 : Mga Kuwento ni Lola Basyang. (ABS-CBN.)
Natalia runs away before her parents announce her arranged marriage to Crisostomo, their rich haciendero neighbor. She hides in the forest and disguises herself as a boy, Nato.